Bio-Synthesis and Characterization of CuO and Ag doped CuO nanoparticles using Cissampelos Pareira and their Anti-cancer applications - H. R. Uma; Jessica Fernando (The Bioscan, 2025)
This research aimed to evaluate the antitumor efficacy of these nanoparticles against AGS cancer cells. Pure CuO and Ag-doped CuO nanoparticles were produced and studied using X-ray diffraction (XRD), energy-dispersive spectroscopy (EDS), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), and UV-visible spectroscopy. The anti-cancer efficacy of the biogenically produced nanoparticles was assessed against AGS cancer cells. The produced Pure CuO and Ag-doped CuO nanoparticles and plant extract characterised displayed a lethal effect on AGS cancer cells. In addition to these exciting discoveries, the materials deactivate against an AGS cell line by an MTT trial, which revealed the superiority of the doped as compared to the native nanoparticles. As a consequence, these findings revealed that the produced biogenic nanoparticles are suitable candidates for cancer therapy in the biomedical area as an anticancer agent.